Optimal SHE-PWM Technique for Three-Level Voltage Source Converter Control - M. S. A., Dahidah; V. G., Agelidis (PRAISE WORTHY PRIZE SRL, 2008)
Selective harmonic elimination pulse-width modulation (SHE-PWM) technique for three-level voltage source converter is presented in this paper. It is mathematically defined using Fourier-based equations to describe the output voltage waveform. An efficient minimization technique assisted with hybrid genetic algorithm is then applied to obtain the optimal switching angles. Different operating points including single- and three-phase systems are presented to demonstrate the effectiveness of the proposed method Selected simulation and experimentally validated results are reported to show the effectiveness of the proposed method Copyright (C) 2008 Praise Worthy Prize S.r.l. - All rights reserved.